2021
DOI: 10.3390/cancers13040870
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immune Evasion Induced by Dysregulation of Erythroid Progenitor Cells Development

Abstract: Cancer cells harness normal cells to facilitate tumor growth and metastasis. Within this complex network of interactions, the establishment and maintenance of immune evasion mechanisms are crucial for cancer progression. The escape from the immune surveillance results from multiple independent mechanisms. Recent studies revealed that besides well-described myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) or regulatory T-cells (Tregs), erythroid progenitor cells (EPCs) play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 317 publications
3
26
0
3
Order By: Relevance
“…As known, hemoglobin levels have a prognostic role in cancers ( 41 ) and are predictive for response to various anti-cancer therapies, especially when combined with albumin, lymphocyte, and platelet levels ( 42 ). It has been also reported that, regardless of its causes, hemoglobin levels could influence the activation status of T cells against cancer ( 43 , 44 ). Other authors also reported an association between higher hemoglobin levels and better clinical outcomes both in CSCC and lung cancer patients treated with PD-1 inhibitor ( 24 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…As known, hemoglobin levels have a prognostic role in cancers ( 41 ) and are predictive for response to various anti-cancer therapies, especially when combined with albumin, lymphocyte, and platelet levels ( 42 ). It has been also reported that, regardless of its causes, hemoglobin levels could influence the activation status of T cells against cancer ( 43 , 44 ). Other authors also reported an association between higher hemoglobin levels and better clinical outcomes both in CSCC and lung cancer patients treated with PD-1 inhibitor ( 24 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The systemic immunity in cancer beyond the TME is essential for effective immune response toward immunotherapy, and the tumor immune macroenvironment is remarkably plastic (2)(3)(4). Recently, immature red blood cells called CD71 + erythroid progenitor cells (CECs) or erythroid progenitor cells (EPCs) were identified as regulators of the immune response in cancer (5,6). The CD71/Ter119 combination-marked CECs reflect the dynamic maturation of red blood cells, which define the nucleated erythrocytes (7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CECs at the earliest stages of differentiation are relatively rare in healthy individuals 45 . Thus, it seems that CECs may have the most significant immunoregulatory role under conditions that are characterized by the impaired erythroid differentiation and robust enrichment of early-stage CECs, that include cancer 55 .…”
Section: Discussionmentioning
confidence: 99%